Navigating challenges and bridging gaps: Evaluating the 95-95-95 targets of UNAIDS in Northeast India’s seven sister states - Arushi Arya; T. P. Sherin Raj; Vijay Kumar Tiwari (Indian Journal of Community and Family Medicine, 2025)
Introduction: The UNAIDS 95-95-95 targets are part of a global strategy to end the AIDS epidemic by 2030. These targets aim for 95% of PLHIV to know their status, 95% of diagnosed individuals to receive antiretroviral therapy (ART), and 95% of those on treatment to have suppressed viral loads. The study aims to project the achievement for the year 2025 based on available data from 2018 to 2021 to ascertain the progress made toward the UNAIDS 95-95-95 targets in the seven northeastern sister states of India. Material and Methods: The methodology adopted for this article is a combination of secondary data sources and literature reviews. The main source of information is the National AIDS Control Organization Annual Sankalak Report 2022. Results: Tripura is expected to achieve the target of 95-95-95 in the near future, and the other states have varying degrees of gaps to bridge. With the current pace of achievements, states of Manipur and Meghalaya will be achieving the target in the year 2060 and 2059, respectively. Arunachal Pradesh, Assam, and Nagaland also have substantial gaps, expected to achieve target in the year 2042, 2034, and 2042, respectively. Conclusion: The main causes of high prevalence of HIV/AIDs may be higher percentage of injectable drug use, less ART coverage, and less comprehensive knowledge. Factors contributing to the gaps may include inadequate infrastructure, socioeconomic challenges, policy implementation gaps, and resource allocation disparities. The data highlight the higher prevalence of HIV/AIDS among injecting drug user in the northeastern states compared to female sex workers and men who have sex with men and are far behind the targets except Tripura. Therefore, efforts should be made to address these challenges, focusing on enhancing education, health care, infrastructure development, and socioeconomic opportunities.